Whitehead's pancreativism : the basics - Weber, Michel, 1963- (Process thought, 2006)
There is one question that any potential reader who suspects that Alfred North Whitehead (1861-1947) might be important for past, contemporary, and future philosophy inevitably raises: how should I read Whitehead? How can I make sense of this incredibly dense tissue of imaginative systematizing, spread over decades of work in disciplines so different and specialized as algebra, geometry, logic, relativistic physics and philosophy of science? Accordingly, this monograph has two main complementary objectives. The first one is to propose a set of efficient hermeneutical tools to get the reader st.